CD43 is an adverse prognostic factor in newly diagnosed multiple myeloma. Issue 11 (19th September 2022) - Ning, Xueqin; Wei, Xiaolei; Chen, Bingyuan; Li, Zhen; Zheng, Zhongxin; Yi, Zhengshan; Wei, Qi; Guo, Xutao; Kang, Qiaoxi; Feng, Ru; Wei, Yongqiang
Abstract: Currently, the expression pattern and prognostic value of CD43 expression in multiple myeloma (MM) remain unknown. 109 newly diagnosed MM patients were recruited and CD43 expression was determined by multiparameter flow cytometry, of which 77 (70.6%) were CD43 positive. Patients with positive CD43 expression were more likely to present with, hemoglobin < 85 g/L ( p  = 0.008), International Staging System (ISS) stage III ( p  = 0.044), 13q14 deletion ( p  = 0.034) and more monoclonal plasma cells ( p  = 0.003). Patients with CD43 positive had significantly poor treatment response ( p  = 0.021), progression-free survival (PFS) ( p  = 0.012), and overall survival (OS) ( p  = 0.023) than those without CD43. The poorer prognosis of CD43-positive patients was retained in multivariate analysis ( p  = 0.005 for PFS; p  = 0.013 for OS). Our study indicated that CD43 was an independent adverse prognostic factor in multiple myeloma.